Impact of Endocrine Disruptors on the Genitourinary Tract - Christophe Caneparo; Laurence Carignan; Elena Lonina; Sarah-Maude Goulet; Felix-Antoine Pellerin; Stéphane Chabaud; François Bordeleau; Stéphane Bolduc; Martin Pelletier (Journal of Xenobiotics)
Over the last decades, the human species has seen an increase in the incidence of pathologies linked to the genitourinary tract. Observations in animals have allowed us to link these increases, at least in part, to changes in the environment and, in particular, to an increasing presence of endocrine disruptors. These can be physical agents, such as light or heat; natural products, such as phytoestrogens; or chemicals produced by humans. Endocrine disruptors may interfere with the signaling pathways mediated by the endocrine system, particularly those linked to sex hormones. These factors and their general effects are presented before focusing on the male and female genitourinary tracts by describing their anatomy, development, and pathologies, including bladder and prostate cancer.